The Effect of Work-Family Conflict, Work Engagement and Workload on Turnover Intention on Nurses of XYZ Hospital, Bogor District - Jeremy Jovanie Owen; Yohana F. Cahya Palupi Meilani (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze the effect of work-family conflict on turnover intention. 2). Work Engagement on Turnover Intention. 3). Workload against Turnover Intention for Nurses at XYZ Hospital, Bogor District. The analysis was carried out using a quantitative research method approach, through statistical analysis calculations and measurements using SmartPLS software version 3.3, and the results obtained that Work-Family Conflict has a positive effect on Turnover Intention, Work Engagement has a negative effect on Turnover Intention, and Workload has a positive effect on Turnover Intention.